Intellectual capital in Malaysian hotel industry: A case study of Malacca - Muhammad, Khalique; Shazali, Abu Mansor (Inderscience Enterprises Ltd., 2016)
Intellectual capital is recognised as a crucial strategic asset that provides organisations with a competitive edge and sustainable growth in a cutthroat business environment. There is an increasing comprehension that intellectual capital is critical to organisational performance, this is still an emerging area of inquiry in tourism industry in Malaysia. Therefore, this study was undertaken with the aim to demonstrate the impact of intellectual capital on the organisational performance of hotel industry operating in Malacca, Malaysia. Six components of intellectual capital were used in the study. A total of 193 individuals were involved in this study to test the proposed research hypotheses. The results of multiple regression analysis demonstrated that four out of seven research hypotheses were supported. This study will extend the understanding of the concept and applications of intellectual capital in hotel industry in Malaysia. Moreover, this study will be a milestone for the potential researchers to conduct their further studies in hotel industry.